Does Political Connection, Executive Character, and Audit Quality Affect the Tax Avoidance Practice? Evidence in Indonesia - Diah Amalia; Steven Ferdiansyah (Sebelas Maret Business Review, 2019)
This study aims to know and find empirical evidence about the effect of political connection, executive characters, and audit quality on tax avoidance practice in Indonesia. This research uses secondary data with database collection technique using annual report of the manufacturing companies that are listed in Indonesian Stock Exchange (IDX) period 2013 – 2017. Using purposive sampling, this study obtained 51 companies which fulfill the criteria of 165 companies as total population, so the total observation for 5 years is 255 samples. The data examination in this study uses multiple regression analysis with data panel. Tax avoidance practice in this research proxied by Cash ETR. The results of this study indicate that variable political connection has significant positive effect on tax avoidance, which means that the average company uses their political connections to lower tax payments. Variable executive characters has no significant effect on tax avoidance, which means that the characters of executive not yet able to become a standard to determining tax avoidance practice. Variable audit quality indicated no significant effect on tax avoidance, which means KAP the big four who has a good quality hasn’t been able to conclude the company not doing tax avoidance practice.